The Times : bridging the old with the new - Alsfine, Karen; Mosala, Thabo ([London] : SAGE, 2016)
It was April 2007, and Ray Hartley still had myriad unanswered questions in the lead-up to the launch of a new daily newspaper, The Times, in June 2007. As the editor, he debated whether the paper, with its online functionality, would be targeting a brand new market or actually be merely an extension of The Sunday Times' existing market of over 130,000 subscribers. This text looks at how Hartley would come to resolve this issue.
Originally Published in: Alsfine, K., & Mosala, T. (2009). The Times - Bridging the Old with the New. WBS-2009-4. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; New business enterprises -- Case studies